CHAP: A versatile tool for the structural and functional annotation of ion channel pores - Klesse, G; Rao, S; Sansom, M; Tucker, S (Elsevier, 2019)
The control of ion channel permeation requires the modulation of energetic barriers or "gates" within their pores. However, such barriers are often simply identified from the physical dimensions of the pore. Such approaches have worked well in the past,but there is now evidence that the unusual behaviour of water within narrow hydrophobic pores can produce an energetic barrier to permeation without requiring steric occlusion of the pathway. Many different ion channels have now been shown to exploit "hydrophobic gating" to regulate ion flow, and it is clear that new tools are required for more accurate functional annotation of the increasing number of ion channel structures becoming available. We have previously shown how molecular dynamics simulations of water can be used as a proxy to predict hydrophobic gates, and we now present a new and highly versatile computational tool, the Channel Annotation Package (CHAP) that implements this methodology.